How animacy impacts word order in Austrian Sign Language (ÖGS): Evidence from sentences with inanimate subject arguments - Krebs, Julia (Lingua, 2025)
•The subject preference was observed for sentences with inanimate subject arguments.•Animacy does not override the subject preference in ÖGS.•In ÖGS, word order outranks animacy for actor identification.•Animacy may impact word order in ÖGS, revealing an interplay of syntax and semantics. Cross-linguistic evidence shows that the animacy of event participants may impact the syntactic structure in language production. This study examines the effect of animacy on word order and the previously observed preference for subject-initial orders in Austrian Sign Language (ÖGS). Therefore, word order in two sets of transitive sentences with inanimate subject arguments was tested by a production task. In particular, word order was examined in structures with an inanimate subject and an animate object argument, as well as in sentences with two inanimate arguments. Deaf fluent signers were asked to sign event descriptions elicited by stimuli that included a picture illustrating the subject argument, a picture showing the object argument, and a verb presented as a written gloss. Data analysis provides support for SOV as the basic order in ÖGS and demonstrates the robustness of the subject preference, even in sentences with inanimate subject arguments. Furthermore, while animacy does not override the subject preference in ÖGS, the data suggest that it may still influence word order in this language.